2007
DOI: 10.1038/nmat2012
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial integration of the highly spin-polarized ferromagnetic semiconductor EuO with silicon and GaN

Abstract: Doped EuO is an attractive material for the fabrication of proof-of-concept spintronic devices. Yet for decades its use has been hindered by its instability in air and the difficulty of preparing and patterning high-quality thin films. Here, we establish EuO as the pre-eminent material for the direct integration of a carrier-concentration-matched half-metal with the long-spin-lifetime semiconductors silicon and GaN, using methods that transcend these difficulties. Andreev reflection measurements reveal that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
277
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(295 citation statements)
references
References 40 publications
10
277
2
1
Order By: Relevance
“…9 Recent studies of spin-resolved x-ray absorption spectroscopy have shown a spin-split conduction band of about 0.6 eV in its ferromagnetic state, creating a nearly 100% spin polarized electrons close to the conduction band edge. 10 Although the stoichiometric EuO has a Curie temperature (Tc) of 69 K, Tc can be enhanced significantly by pressure, [11][12][13] interfacial strain 14 or electron doping via rare-earth atoms [15][16][17][18][19][20][21][22][23][24] or oxygen vacancies. 15,16,[23][24][25] The integrations of EuO with Si, 18,[23][24][25][26][27] GaAs, 28 and GaN 18 have been successfully demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recent studies of spin-resolved x-ray absorption spectroscopy have shown a spin-split conduction band of about 0.6 eV in its ferromagnetic state, creating a nearly 100% spin polarized electrons close to the conduction band edge. 10 Although the stoichiometric EuO has a Curie temperature (Tc) of 69 K, Tc can be enhanced significantly by pressure, [11][12][13] interfacial strain 14 or electron doping via rare-earth atoms [15][16][17][18][19][20][21][22][23][24] or oxygen vacancies. 15,16,[23][24][25] The integrations of EuO with Si, 18,[23][24][25][26][27] GaAs, 28 and GaN 18 have been successfully demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] A particularly attractive candidate ferromagnetic semiconductor is europium oxide (EuO), which is known to possess nearly spin-polarized bands. 85,86 EuO becomes ferromagnetic below 70K under ambient pressure and the Curie temperature is known to increase with pressure reaching 200K under 1.5 × 10 5 atmospheres. 87 Since its integration with with Si and GaN, 86 EuO has garnered much attention for its potential use in spintronic applications.…”
Section: Topological Superconductivity and Majorana Fermionsmentioning
confidence: 99%
“…85,86 EuO becomes ferromagnetic below 70K under ambient pressure and the Curie temperature is known to increase with pressure reaching 200K under 1.5 × 10 5 atmospheres. 87 Since its integration with with Si and GaN, 86 EuO has garnered much attention for its potential use in spintronic applications. Ferromagnetic superconductors are materials that exhibit intrinsic coexistence of superconductivity and ferromagnetism where the same electrons are believed to be superconducting and ferromagnetic simultaneously.…”
Section: Topological Superconductivity and Majorana Fermionsmentioning
confidence: 99%
“…Recently it was shown, that EuO can be epitaxially grown on Si and GaN, which opens new possibilities for device realization. 4,43 …”
Section: Properties Of Europium Chalcogenidesmentioning
confidence: 99%
“…Current interest in EuX magnetic semiconductors arises from potential applications for spintronics and magneto-optical devices. 4,5 Their nonlinear optical and magneto-optical properties, however, remained unexplored until recently when magnetic-field-induced second-harmonic generation ͑SHG͒ was observed in EuTe, EuSe, 6,7 and in EuO. 8 Nonlinear optics is a large, continuously expanding field of fundamental and applied research.…”
Section: Introductionmentioning
confidence: 99%